PENGARUH SERVQUAL TERHADAP LOYALITAS NASABAH DENGAN KEPUASAN SEBAGAI PEMEDIASI STUDI PADA BANK DAERAH DI YOGYAKARTA - Andalas, Purwani Retno; Putra, Alfa Santoso B (KINERJA, 2014)
This study aims to analyze the impact of servqual to customer loyalty with customer satisfaction as the intermediary variable on regional bank BPR and BPD in Yogyakarta. Simple regression, multiple regression, and path analysis are used as the analysis tools. This study indicates that servqual significantly affects to customer satisfaction, customer loyalty of regional bank. Furthermore, customer satisfaction also significantly affects to customer loyalty of regional bank and the interaction of servqual impact to customer loyalty moderated by customer satisfaction.Keywords: servqual, customer satisfaction, customer loyalty, regional bank